FAKTOR-FAKTOR YANG MEMPENGARUHI PERKEMBANGAN UMKM DI SURAKARTA - Hartono Hartono; Deny Dwi Hartomo (Jurnal Bisnis dan Manajemen (Journal of Business and Management), 2014)
Micro, Small and Medium Enterprises (MSMEs) have a very significant impact on the Indonesian economy. Therefore, it is important to do research in order to determine the condition of current performance and analyze the factors that influence the development of MSMEs and to provide strategic advice on the development of MSMEs in Surakarta. Long-term goal is the development of MSMEs in Surakarta in the future as measured from the increase in sales, so the SMEs entrepreneurs increase revenue, reduce unemployment and ultimately can reduce the level of poverty in Surakarta by particular and Indonesia by general.The study took a sample of 91 MSMEs entrepreneurs spread across five districts in the city of Surakarta. Each district taken by SMEs entrepreneurs with purposive sampling method. Mapping MSMEs performance conditions were analyzed descriptively to describe various aspects such as firm age, labor, raw materials, capital and problems faced. While the factors that influence the development of MSMEs were statistically analyzed with multiple regression models.The results showed that the performance of the mapping conditions of SMEs in Surakarta average face problems in raw material costs, labor costs and promotion costs, as well as in the capital. Capital cost and total variable evidenced by the positive and significant impact on the development of the business. While the age factor and the company's workforce does not have a significant influence on the development of SME. It can be understood that the main problem in SMEs are raw materials and capital. There is a type of business that is not easy to obtain raw materials in the market. Therefore SME development strategy with more emphasis on the supply of raw material, marketing, production, and capital.